Respuesta :
Answer:
The correct answer is (5, -4)
Step-by-step explanation:
To solve using substitution, we can take the second equation (y = -3x + 11) and use the value of y to replace y in the first equation. This will allow us to solve for x.
3x + 2y = 7
3x + 2(-3x + 11) = 7
3x - 6x + 22 = 7
-3x + 22 = 7
-3x = -15
x = 5
Now that we have that value, we can put it in for x in either equation and solve for y.
y = -3x + 11
y = -3(5) + 11
y = -15 + 11
y = -4
Therefore the correct answer is (5, -4)